Programa de control de exposición a vibraciones en cuerpo entero, a ruido y ergonómico en los operarios del Quebredor OchomogoOGO LTDA. - Granados-Castillo, Reina (Instituto Tecnológico de Costa Rica, 2018)
The present project was carried out in the Quebrador Ochomogo LTDA, specifically in the area of heavy machinery, in the tasks of extraction, crushing and dispatch, as well as in the maintenance workshop. Due to the nature of the process, operators of heavy machinery are exposed to vibrations, noise and ergonomic risk factors. The type of research that was carried out is of applied type, since the acquired knowledge was applied and used. The methodology used in the case of vibrations will be UNE-EN ISO 2631-1-1997 for whole body exposure, in the case of noise corresponds to the INTE / ISO 9612 and the ergonomic part, tools were used for risk assessment such as REBA and RULA. The general objective of the project is to propose a program of control of exposure to vibrations, noise and ergonomic in the operators of the Quebrador Ochomogo LTDA, this in order to increase controls and prevent accidents, injuries or occupational diseases in this occupation. The obtained results reflect that the collaborators use positions that compromise the different parts of the body and that it can bring future consequences, in the case of the vibrations the highest results obtained by the measurements were 0.73 m / s2 (A (8)) and 11.10 m / s1.75 (VDV) in both cases the z-axis predominates, these operators acquire postures such as trunk and neck torsion. In noise, all employees exceed the values established by the regulations. With the different methodologies it was obtained that the collaborators are exposed to whole body vibrations, noise and ergonomic factors that can affect their health. Among the recommendations given is to inspect the correct use of the central and side mirrors, implementation of seats with shock absorbers, use of hearing protection equipment, among others.
Proyecto de graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2018.
Keywords: Vibración; Ruido; Ergonomía; Valor; Límites; Acciones; Posturas; Riesgos; Research Subject Categories::MEDICINE::Social medicine::Public health medicine research areas::Occupational medicine